2022
DOI: 10.21203/rs.3.rs-2274148/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergency Departments as Under-Utilized Venues to Provide HIV Prevention Services to Female Sex Workers in Nairobi, Kenya

Abstract: Background: Female sex workers (FSW) in sub-Saharan Africa are disproportionately affected by HIV and remain a key target population for efforts to reduce transmission. While HIV prevention tools such as PEP and PrEP are available through outpatient FSW clinics, these services are underused. Emergency medicine is a rapidly expanding field in Kenya and may provide a novel venue for initiating or optimizing HIV prevention services. This study examined the characteristics of FSW from Nairobi, Kenya who had utiliz… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Globally, MSM, transgender people, and PWID populations are at a high risk for injury in the forms of interpersonal violence, sex-based violence and victimization, homicide, nonsuicidal self-harm, and suicide [17,18]. A HIV screening program in Kenya targeting FSW found that those who had received emergency care in the past year had higher prevalence of HIV risk factors as well as client-perpetrated sexual violence [19]. Country wide representative data collected by the National AIDS and STIs Control Program in Kenya also showed high prevalence of violence experienced by FSW (48%), PWID (44%), and MSM (20%) [20].…”
mentioning
confidence: 99%
“…Globally, MSM, transgender people, and PWID populations are at a high risk for injury in the forms of interpersonal violence, sex-based violence and victimization, homicide, nonsuicidal self-harm, and suicide [17,18]. A HIV screening program in Kenya targeting FSW found that those who had received emergency care in the past year had higher prevalence of HIV risk factors as well as client-perpetrated sexual violence [19]. Country wide representative data collected by the National AIDS and STIs Control Program in Kenya also showed high prevalence of violence experienced by FSW (48%), PWID (44%), and MSM (20%) [20].…”
mentioning
confidence: 99%